2014
DOI: 10.1007/s10071-014-0830-4
|View full text |Cite
|
Sign up to set email alerts
|

Wild vervet monkeys copy alternative methods for opening an artificial fruit

Abstract: 18Experimental studies of animal social learning in the wild remain rare, especially those that The option preferred in all 13 monkey's first successful manipulation session was highly 27 correlated with the proportional frequency of that option they had previously witnessed. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…An explanation for the strength of this effect might lie in the fact that ours is so far the only study to seed local habits in a majority of each group. The handful of other field experiments that have seeded alternative behaviors in the wild have typically done so in only single individuals initially, and these studies have tended to demonstrate initial social learning, soon followed by corruption and erosion of group behaviors, rather than the resilience so marked in our own study where we instead simulated existing customary traditions (Kendal et al, ; Schnoell & Fichtel, ; Thornton & Malapert, ; van de Waal et al, ). Another potential explanation is that our experiment is the only one testing a preference for a food type rather than including an object or “artificial fruit” manipulation like those cited above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An explanation for the strength of this effect might lie in the fact that ours is so far the only study to seed local habits in a majority of each group. The handful of other field experiments that have seeded alternative behaviors in the wild have typically done so in only single individuals initially, and these studies have tended to demonstrate initial social learning, soon followed by corruption and erosion of group behaviors, rather than the resilience so marked in our own study where we instead simulated existing customary traditions (Kendal et al, ; Schnoell & Fichtel, ; Thornton & Malapert, ; van de Waal et al, ). Another potential explanation is that our experiment is the only one testing a preference for a food type rather than including an object or “artificial fruit” manipulation like those cited above.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, founder models are trained to perform alternative behavioral solutions to naturalistic foraging problems and allowed to perform these within their group, with it being “open” who watches and potentially learns from what is modelled, and the subsequent behavior of observers is monitored through further experimental presentations. Although only a few such studies have been completed in the wild, they have delivered positive evidence of diffusion, in birds (Aplin, Sheldon, & Morand‐Ferron, ; Aplin et al, ), meerkats (Thornton & Malapert, ) and monkeys (van de Waal, Claidière, & Whiten, ). However, the evidence for longevity in the alternatives that start to diffuse, and hence form incipient traditions, is more mixed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of multiple groups of wild primates within single populations have demonstrated social learning through field experiments (in four groups of lemurs, Schnoell & Fichtel, ; in up to 13 groups of marmosets, Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold Whiten, & Bugnyar, ; in up to six groups of vervet monkeys, van de Waal et al, ; van de Waal et al, ; van de Waal, Borgeaud, et al, ; de Waal et al, ; de Waal, Claidière, & Whiten, ; van de Waal & Bshary, ). However, long‐term observations of these populations, with the aim of revealing potential intergroup differences, are to my knowledge lacking, until this present review of behavioural variation in wild vervet monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…1). The box was similar to that used with vervet monkeys ( Chlorocebus pygerythrus ), but modified so that there was only one option to open the door: sliding it with a handle (van de Waal et al 2013, 2015). We attached the box either to a foraging platform or to branches at human chest level.…”
Section: Methodsmentioning
confidence: 99%